In vitro biofilm formation by multidrug resistant clinical isolates of Pseudomonas aeruginosa - Sanjee, Sohana Al; Hassan, Md Mahamudul; Manchur, MA (Asian Journal of Medical and Biological Research, 2018)
In this study, 15 isolates of Pseudomonas aeruginosa were recovered in Cetrimide agar medium from aseptically collected swab samples. Antibiotic susceptibility test revealed highest resistance against Rifampicin (100%) followed by Penicillin (80%), Erythromycin (73.33%), Cephalosporin group (13.33-60%) and Aminoglycoside group (26.67%). The most effective group of antibiotic was Carbapenem with 6.67% resistance. Among 15 isolates, 3 were having highest Multiple Antibiotic Resistance (MAR) index were identified as Pseudomonas aeruginosa (P1, P2 and P3) by API®20NE microbial identification kit. Minimum inhibitory concentration (MIC) of the isolates P1, P2 and P3 was 3.05μg/mL, 0.76μg/mL and 3.05μg/mL for Meropenem whereas for Ceftriaxone it was 12.207μg/mL, 12.207μg/mL and 781.25μg/mL, respectively. Minimum bactericidal concentration (MBC) of Meropenem and Ceftriaxone was same for the isolates P1 and P2 i.e., 48.83μg/mL and 195.313μg/mL, respectively but in case of P3 it was 781.25μg/mL for both antibiotics. In case of 70% ethanol, the MIC and MBC was 1:4 dilutions (for isolate P3, MBC was 1:2 dilutions) whereas for Savlon®, MIC and MBC was 1% and 2% solution, respectively. All of the three isolates were biofilm former according to test tube assay and microtitre plate assay whereas modified congo red agar assay indicated only one isolate as biofilm former. The results suggest that post-operative wound infection may serve as a reservoir for multidrug resistant biofilm forming P. aeruginosa which may complicate the treatment regime unless proper treatment ensured based on antibiotic/antiseptic susceptibility test. Asian J. Med. Biol. Res. March 2018, 4(1): 105-116